Proceedings of the 23rd International Conference on World Wide Web 2014
DOI: 10.1145/2567948.2576960
|View full text |Cite
|
Sign up to set email alerts
|

Crowd vs. experts

Abstract: The results of our exploratory study provide new insights to crowdsourcing knowledge intensive tasks. We designed and performed an annotation task on a print collection of the Rijksmuseum Amsterdam, involving experts and crowd workers in the domain-specific description of depicted flowers. We created a testbed to collect annotations from flower experts and crowd workers and analyzed these in regard to user agreement. The findings show promising results, demonstrating how, for given categories, nichesourcing ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…e KIC intermediaries are typical two-or multisided markets, where the network effects will attract an increasing number of participants from both supply and demand sides, to join the platform for valuable advantages [26]. Oosterman et al [27] suggested that the KIC has the advantage of low cost for service requesters; therefore, it allows cost-saving and efficient use of resources. Additionally, by inviting a crowd of customers to new product development through a crowdsourcing practice, taking Dell IdeaStorm [28] for example, innovative product or service ideas can be generated and then applied to the production process, thus making the products more attractive to markets and adding value to companies' business [19].…”
Section: Knowledge-intensivementioning
confidence: 99%
“…e KIC intermediaries are typical two-or multisided markets, where the network effects will attract an increasing number of participants from both supply and demand sides, to join the platform for valuable advantages [26]. Oosterman et al [27] suggested that the KIC has the advantage of low cost for service requesters; therefore, it allows cost-saving and efficient use of resources. Additionally, by inviting a crowd of customers to new product development through a crowdsourcing practice, taking Dell IdeaStorm [28] for example, innovative product or service ideas can be generated and then applied to the production process, thus making the products more attractive to markets and adding value to companies' business [19].…”
Section: Knowledge-intensivementioning
confidence: 99%
“…Traditionally, new knowledge can be acquired through research and learning (Huber 1991) and/or by hiring new employees (Davenport and Prusak 2000) with distinct knowledge and expertise, evidenced by their curriculum and qualifications. In citizen science, however, recruiting can be either to acquire new knowledge and learn from the public (Afuah and Tucci 2012; Oosterman et al 2014) or to access and use specific skills of the public.…”
Section: Accessing Versus Acquiring Knowledgementioning
confidence: 99%
“…The early work [27] defined the problem of artwork annotation in the context of the Rijksmuseum Amsterdam in the Netherlands. The subsequent works [8,28] introduced an experimental methodology, and reports on preliminary results mainly focused on Artwork-centric knowledge extraction. To the best of our knowledge, our work is the first one that systematically studies the performance of Artwork-centric and Class-centric knowledge extraction techniques in human computation platforms, and assess their identification and location performance with respect to a high-quality ground truth.…”
Section: Related Workmentioning
confidence: 99%
“…Crowdsourced artwork annotation is a representative example of a Crowdsourced Knowledge Creation (CKC) task [8], i.e. a class of crowdsourcing tasks where workers are requested to stress their highlevel cognitive abilities (e.g., knowledge synthesis, data interpretation), and draw from their experience or education, in order to solve problems for which a unique, factual solution might not exist.…”
Section: Introductionmentioning
confidence: 99%